2021
DOI: 10.1371/journal.pone.0258227
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal community structure and seasonal diversity following application of organic amendments of different quality under maize cropping in Zimbabwe

Abstract: Recent advocacy for Integrated Soil Fertility Management (ISFM) in smallholder farming systems in east and southern Africa show substantial evidence of increased and sustained crop yields associated with enhanced soil productivity. However, the impact ISFM on soil fungi has received limited attention, yet fungi play key roles in crop growth. Following total soil DNA extraction with ZR soil microbe miniprep kit, illumina sequencing was used to, examine the fungal communities (ITS1F) under a maize crop following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…The number of fungi belonging to Ascomycota may decrease as the organic matter in the soil is degraded. Other fungi, for example, Mortierellomycota or Basidiomycota, may take up these organics for growth, resulting in nutrient depletion and the inhibition of Ascomycota growth [87]. In addition, our study showed that spring wheat and spring rapeseed used as the previous crops positively affected the development of the Mortierella genus fungi, winter wheat positively affected the development of Cladosporium fungi, and maize positively affected the development of Alternaria fungi.…”
Section: Bacterial and Fungal Communitiesmentioning
confidence: 65%
“…The number of fungi belonging to Ascomycota may decrease as the organic matter in the soil is degraded. Other fungi, for example, Mortierellomycota or Basidiomycota, may take up these organics for growth, resulting in nutrient depletion and the inhibition of Ascomycota growth [87]. In addition, our study showed that spring wheat and spring rapeseed used as the previous crops positively affected the development of the Mortierella genus fungi, winter wheat positively affected the development of Cladosporium fungi, and maize positively affected the development of Alternaria fungi.…”
Section: Bacterial and Fungal Communitiesmentioning
confidence: 65%
“… Xie and Yin (2022) showed that soil fungal diversity and richness in broad-leaved forests were higher than those in conifer forests. Fungal community diversity and composition are significantly driven by soil pH, available nitrogen, available phosphorus, moisture, organic carbon, fine root biomass and root tissue density ( Beauregard et al, 2010 ; Zhou et al, 2016b ; Tauro et al, 2021 ). Soil pH is the dominant driver that is significantly related to fungal alpha diversity ( Wang et al, 2015 ; Adamo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…SOC may affect the structure of the soil fungal community ( Sul et al, 2013 ; Li et al, 2017 ), because the abundance of cellulose-degrading fungi may be linked to SOC fractions and may respond to changes in SOC fractions differently. Soil available phosphorus and nitrogen are influential factors shaping fungal communities ( Tauro et al, 2021 ). In a previous study, the fungal community was less strongly affected by pH, because fungi generally exhibit wide pH ranges for optimal growth ( Rousk et al, 2010 ; Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PCR reaction system (20 μL) for bacteria included 4 μL of 5 × FastPfu buffer, 2 μL of 2.5 mM dNTPs, 0.8 μL of each primer (5 μM), 0.4 μL of TransStart FastPfu DNA Polymerase (TransGen, Beijing, China), 0.2 μL of BSA and 10 ng of Template DNA. Meanwhile, to identify the characteristics of fungal communities, the internal transcribed spacer 1 (ITS1) region of the ribosomal RNA gene was amplified using primers ITS1F (5′-CTTGGTCATTTAGAGGAAGTAA-3′) and ITS2R (5′-GCTGCGTTCTTCATCGATGC-3′) ( Tauro et al, 2021 ). The PCR reaction system (20 μL) for fungi included 2 μL of 10 × buffer, 2 μL of 2.5 mM dNTPs, 0.8 μL of each primer (5 μM), 0.2 μL of TaKaRa rTaq DNA Polymerase (Takara, Shiga, Japan), 0.2 μL of BSA and 10 ng of Template DNA.…”
Section: Methodsmentioning
confidence: 99%